PENGEMBANGAN SISTEM PENDIDIKAN PESANTREN DALAM MENINGKATKAN PROFESIONALISME SANTR - Nurotun Mumtahanah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2015)
Islamic boarding schools (pesantren) have served as an institutionproducing not only clerics or religious leaders, but also the nation's pious leadersand professionals engaged in a particular field and imbued with the spirit ofreligious morality as aspired by the national education. On account of thedevelopment of pesantren education system, students (santri) are required tohave a strong commitment to professionalism in carrying out their duties asMulism preachers. one is said to be a professional for inherently having a highdedicative attitude to his tasks, his commitment to process, working andcontinuing qualities, by always improving and updating his models or ways ofworking in accordance with the demands of his day. Pesantren education systemhas integrated elements between Islam, the Indonesianess and science. Suchintegrated education system is projected as an alternative to address the civilsociety demands. The santri professionalism is a commitment to study Islamicand general disciplines in pesantren in addition to mastering various disciplinesas life provision in the community later. So they are expectedly be capable offacing any challenges in this global era. On this stand, the santri professionalismshould always be improved as capital in upholding Islam in the midst of a rapidlygrowing and changing life.